2012
DOI: 10.1002/ccd.23343
|View full text |Cite
|
Sign up to set email alerts
|

Duration of balloon inflation for optimal stent deployment: Five Seconds Is Not Enough

Abstract: The duration of stent balloon inflation has a significant impact on stent expansion. Stent deployment for >25 sec is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The SCAAR definition corresponds to definite stent thrombosis but excludes non-occlusive stent thrombosis. The SCAAR does not hold information on the duration of stent inflation, a parameter closely related to proper stent expansion [24]. The ratio between vessel diameter and balloon diameter was not available and neither was the number of post-dilatations.…”
Section: Discussionmentioning
confidence: 99%
“…The SCAAR definition corresponds to definite stent thrombosis but excludes non-occlusive stent thrombosis. The SCAAR does not hold information on the duration of stent inflation, a parameter closely related to proper stent expansion [24]. The ratio between vessel diameter and balloon diameter was not available and neither was the number of post-dilatations.…”
Section: Discussionmentioning
confidence: 99%
“…To provide a comparison of fixed duration inflation strategies two separate sensitivity analysis were performed—one excluding the study by Cook and the other excluding studies by Cook and Ann. Further, in the studies by Hovasse and Saha, three different inflation times (5, 15, 25 sec and 10, 30, 60 sec, respectively) were evaluated . MSD in the shortest and longest time groups was compared in our meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%
“…17 As for inflation time, Hovasse et al reported that a longer duration of stent balloon inflation (>25 s) significantly improved stent expansion compared with a shorter duration (5 or 15 s). 18 Repeated balloon expansion also improved stent expansion. 19 Kitahara et al recently demonstrated with various metallic platforms assessed by real-time OCT in an in-vitro Accordingly, a dedicated implantation technique needs to be used for implantation of the Absorb BVS to achieve a similar acute performance as the metallic stent.…”
Section: Impact Of Implantation Technique On Scaffold Expansionmentioning
confidence: 96%